Light at the ENDothelium-role of Sox17 and Runx1 in endothelial dysfunction and pulmonary arterial hypertension - Simmons Beck, Robert; Liang, Olin D.; Klinger, James R. (Frontiers in Cardiovascular Medicine, 2023)
Pulmonary arterial hypertension (PAH) is a progressive disease that is characterized by an obliterative vasculopathy of the distal pulmonary circulation. Despite significant progress in our understanding of the pathophysiology, currently approved medical therapies for PAH act primarily as pulmonary vasodilators and fail to address the underlying processes that lead to the development and progression of the disease. Endothelial dysregulation in response to stress, injury or physiologic stimuli followed by perivascular infiltration of immune cells plays a prominent role in the pulmonary vascular remodeling of PAH. Over the last few decades, our understanding of endothelial cell dysregulation has evolved and brought to light a number of transcription factors that play important roles in vascular homeostasis and angiogenesis. In this review, we examine two such factors, SOX17 and one of its downstream targets, RUNX1 and the emerging data that implicate their roles in the pathogenesis of PAH. We review their discovery and discuss their function in angiogenesis and lung vascular development including their roles in endothelial to hematopoietic transition (EHT) and their ability to drive progenitor stem cells toward an endothelial or myeloid fate. We also summarize the data from studies that link mutations in Sox17 with an increased risk of developing PAH and studies that implicate Sox17 and Runx1 in the pathogenesis of PAH. Finally, we review the results of recent studies from our lab demonstrating the efficacy of preventing and reversing pulmonary hypertension in animal models of PAH by deleting RUNX1 expression in endothelial or myeloid cells or by the use of RUNX1 inhibitors. By investigating PAH through the lens of SOX17 and RUNX1 we hope to shed light on the role of these transcription factors in vascular homeostasis and endothelial dysregulation, their contribution to pulmonary vascular remodeling in PAH, and their potential as novel therapeutic targets for treating this devastating disease.